Mother's stress, mood and emotional involvement with the infant: 3 months before and 3 months after childbirth - Figueiredo, Bárbara (2009)
Adverse effects of maternal anxiety and depression are well documented, namely on the foetus/child behaviour and development, but not as much attention has been given to the mother's emotional involvement with the offspring. To study mother's prenatal and postpartum stress, mood and emotional involvement with the infant, the State-Trait Anxiety Inventory, the Edinburgh Postnatal Depression Scale and the Mother-to-Infant Bonding Scale were filled in and cortisol levels were measured, 3 months before and 3 months after childbirth, in a sample of 91 Portuguese women. From pregnancy to the postpartum period, mother's cortisol levels, anxiety and emotional involvement toward the child decrease. No significant change was observed regarding mother's depression. Mother's depression predicted a worse emotional involvement before childbirth, while mother's anxiety predicted a worse emotional involvement with the infant after childbirth. Additionally, pregnant women with a worse emotional involvement with the offspring are at risk of poorer emotional involvement with the infant and higher anxiety and depression at 3 months postpartum. It should be given more attention to mother's poor emotional involvement with the offspring during pregnancy, as it interferes with her emotional involvement with the infant and her psychological adjustment 3 months after childbirth.